Effect of Annealing Temperature on Growth Particles of YAG: Ce +3 Phosphor and White Light Chromaticity Values - Abd., H. R.; Hassan, Z.; Ahmed, N. M.; Omar, A. F.; Alsultany, F. H. (2017)
In the present work white-emitting Y3A15O12:xCe3 (x = 0.04) nanophosphor in the form Of powder were synthesized by a microwave-induced combustion synthesis method (MW) Using metal nitrates as precursors and urea as fuel. By covering blue light-emitting diodes (blue-LED, 445 nm) white light emission (WLED)was generated. The sintering temperature with fixed time (5 hours) for phosphor powder was optimized and found to be 1050 °C. The crystallinity structure, luminescent properties and chromaticity were characterized by X-ray diffraction (XRD), field emission-scanning electron microscope (FE-SEM), electroluminescence (EL) and standard CIE 1931 Chromaticity diagram. The results show that the obtained YAG:Ce+3 phosphor sintered at 1050°C has good crystallinity with pure phase, low agglomeration particles and strong yellow emission that offering daylight white LED with tuneable correlated color temperature (CCT) and a good colour rendering index (CRI) compared to those sintered at 950 °C, 850°C and non-sintered phosphor powders.